(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
At the end of the 15th century, in the 16th century, along with a number of political changes, a unique literary environment emerged in Central Asia. In this regard, the Timurid rulers, who constantly sought to ensure the gathering of the country’s creators, and the Shaibanis in the later stages, left a mark in the history of literature as the biggest patrons of the creators. As a result of the efforts of these dynasties, the establishment of a new school of creativity led to the creation of many works. Especially, the didactic works written in the Sufi tradition have not lost their relevance to this day. It is included in the work “Majmuat ur-rasoil”, which includes 29 treatises written in a mystical-didactic spirit. It is noteworthy that until the creation of the “Majmuat ur-rasoil” collection, there was no collection or anthоlоgy that cоmprehensivеly dоcumеntеd the literary environment of Central Asia or its mysticаl pеrspеctivеs. From this point of view, it can be said that the information about the life and work of Jalaluddin Kosoniy Dahbedi is given a place in this work, which indicates the special place of the poet in this literary environment. Taking into account the above, this article provides brief overview of the textual research of the base manuscript copies of the work “Majmuat ur-rasoil”.